At what BMI are parents of pre-schoolers concerned? - Canterford, L; Wake, M; Hardy, P; Ukoumunne, O (My University, 2011)
Many parents do not recognize that their young children are overweight or obese, possibly because epidemiological cutpoints may not reflect parent perceptions of overweight. We determined whether any Body mass index (BMI) cutpoint reliably triggers parent concern, drawing on the first wave (2004) of the Longitudinal Study of Australian Children (LSAC). BMI (kg/m(2)) and parent concern about their child's weight categorized in three different ways (any, moderately or greater, very) were available for 4,983 children aged 4-5. We used logistic regression to assess the relationship between BMI and parent concern, and receiver operating characteristic (ROC) curves to determine BMI cutpoints that best discriminate parent concern. Parent concern about their pre-schoolers' weight related only modestly to body mass and was not triggered by any definable BMI threshold. This may partly explain why current childhood obesity policies are ineffective, as they typically require individual concern leading to family behavioural change.
Keywords: Children; Health -- Obesity; Health and wellbeing; Health; Children; Obesity; Health and wellbeing